New Onset Coronary Obstruction in Established Nonischemic Heart Failure: A Late Consequence of Radiation - Salil Kumar; Joe Aoun; Arvind Bhimaraj (Methodist DeBakey Cardiovascular Journal)
The column in this issue is provided by Salil Kumar, MD, and Joe Aoun, MD, chief cardiology fellows in the Houston Methodist Cardiology Department, and Arvind Bhimaraj, MD, associate professor of Clinical Cardiology at the Houston Methodist Academic Institute. Dr. Bhimaraj specializes in cardiovascular disease and advanced heart failure and transplantation.